Sistem Informasi Akuntansi Penggajian Guna Menekan Biaya Operasional PT. Eka Prima Mandiri Sentosa Surabaya - Saputri, Thoyyibatul Isnaini; Masyhad, Masyhad; Rosyafah, Siti (Universitas Bhayangkara Surabaya, 2023)
The purpose of this study is to determine and analyze the payroll accounting information system in order to reduce the operational costs of PT Eka Prima Mandiri Sentosa (workshop division AHASS 16272 Eka Prima Mandiri Sentosa Surabaya). This research is a descriptive-qualitative research with a research focus on the payroll accounting information system part cycle. The results of the analysis in this study show that there are still duplicate tasks in the process of making employee payroll, there are no supporting documents for employee overtime submissions, and there are no details of the salary calculations given to employees. In this case, the author draws the conclusion that it is necessary to make updates that are more efficient and effective in the employee overtime submission system in order to reduce more and more operational costs.